Assessing Social Vulnerability to Climate Change in a Fishery-Dependent Village in South Central Vietnam: 10.32526/ennrj/21/20230027 - Olowe, Olumide Samuel; Jacinto, Harliqueen S.; Limbago, Jomel S.; Folorunso, Ewumi Azeez; Sarfo, Isaac; Brown, Christopher (Environment and Natural Resources Journal, 2023)
Fishery-dependent communities are highly susceptible to the impacts of climate change due to their proximity to vulnerable coastal areas and reliance on ecosystem services for their livelihoods. The study assessed the effects of climate change on the socioeconomic livelihoods and adaptive capacity of Xuan Tu, a community located in South Central Vietnam. The assessment employed the social vulnerability index (SVI) and adaptive capacity index (ACI). A hybrid data collection approach was utilized to gather information from households, and a composite method was employed to aggregate the data, enabling an assessment of community vulnerability. The findings indicated exposure, sensitivity, and adaptive capacity index values of 0.16, 0.34, and 0.26, respectively. The community exhibited a moderate vulnerability to climate change, with a social vulnerability index of 0.43. Notably, economic sufficiency, access to social groups, and level of education emerged as significant factors in reducing social vulnerability. To adapt to climate change, the community modified their fish feeding practices, fish culture methods, increased technology usage, and diversified their sources of income. However, the study identified a lack of institutional support as a significant obstacle to the community’s autonomous adaptation. Based on these results, the study recommends livelihood diversification and the implementation of planned adaptation strategies to enhance preparedness for climate emergencies in South Central Vietnam.